Novel approach to assess sarcopenia in children with inflammatory bowel disease - Boros, Kriszta Katinka; Veres, Gábor; Pintér, Hajnalka Krisztina; Richter, Éva; Cseh, Áron; Dezsőfi, Antal; Arató, András; Reusz, George S.; Dohos, Dóra; Müller, Katalin E.; Cseprekál, Orsolya (Frontiers in Pediatrics, 2024)
Introduction: Sarcopenia is associated with poor clinical outcomes in chronic diseases. Our study aimed to characterize body composition (BC) parameters in patients with inflammatory bowel disease (IBD) and compare skeletal muscle mass (SMM) parameters with the healthy pediatric population. Methods: BC of healthy children (HC) and of patients with IBD were measured via multifrequency bioelectrical impedance (InBody 720 device) in a cross-sectional manner. The effect of sex, age, height, weight, and BMI on BC parameters, with a special attention to SMM were assessed. Reference tables from SMM were generated using a maximum-likelihood curve-fitting technique for calculating Z scores. Results: BC parameters associated with age, body size, and sex. SMM was lower in patients with IBD (n=57, aged 6.71±8.7 years) compared to unadjusted HC (n=307, aged 9.9-19.3 years; 143 males; SMM: 22.34±8.38 vs. 24.4±6.3 kg; p=0.03). SMM showed a moderately strong correlation with age, weight, height and BMI (R= 0.65; 0.9; 0.87 and 0.66 p<0.05, for each) in HC. In multivariate stepwise, ridge regression analysis, age, sex, and BMI remained the significant predictors of SMM (age ß=0.47; -0.31 and 0.38 p<0.05, respectively). SMM of sex-age and BMI-adjusted HC did not differ from IBD. Therefore, BMI Z score-based references were plotted for normalizing SMM and SMM Z score was calculated and found to be similar to that of HC. Conclusions: BC is supposed to be an easy-to-measure and objective marker of sarcopenia in children with IBD. Adjustment of SMM for BMI Z score might be needed to avoid the overestimation of sarcopenia in this patient population.